The relationship between professional identity and academic burnout among college students majoring in physical education a chain-mediated effect - Wang, Tianyi; Jiang, Yong (Frontiers in Psychology, 2025)
Previous studies have shown that college students’ professional identity can negatively predict the phenomenon of academic burnout. However, college students majoring in physical education have many differences from other college students in terms of the content and form of learning, and there are fewer related studies, mostly at the level of the employment situation, and very few of them have been conducted on the subjective level of college students majoring in physical education. In addition, we tried to prove the chain mediating role of sports learning interest and achievement motivation in the relationship between professional identity and learning burnout of sports major college students. The respondents in the study, consisted of college students enrolled in physical education majors in the region of China. A total of 551 college students participated, including 383 males and 168 females. The study subjects were all undergraduate college students majoring in physical education. They completed the professional identity scale for undergraduates majoring in physical education, the physical education learning interest scale for undergraduates, the achievement motivation scale, and the learning burnout scale for undergraduates. The results found that there was a significant negative relationship between professional identity and burnout in the group of undergraduates majoring in physical education, and verified the mediating roles of physical education learning interest and achievement motivation. The findings also confirmed the existence of chain mediation among the four variables.